Examining the Inclusion of Natural Disasters in Textbooks Special Primary School for Intellectual Disability - Mansur, Arif Rohman; Sari, Ira Mulya; Herien, Yelly; Deswita, Deswita; Neherta, Meri (International Journal of Disaster Management, 2023)
The children with intellectual disability (ID) are vulnerable to Natural Disasters and need priority protection. This leads to the effective implementation of disaster risk reduction (DRR) through integration in school textbooks (ST) as the primary source of teaching and learning, to provide information to ID children. A significant gap is also observed in understanding the extent and adequacy of Natural Disasters in relevant textbooks, accompanied by the potential analysis of appropriate materials. Therefore, this study aimed to examine the inclusion of Natural Disasters in textbooks implemented for ID primary schools using a qualitative content analysis method. All 2020-2021 academic year books were also effectively and efficiently reviewed in presenting the materials of disasters. Results: Six of the 36 textbooks implemented contained natural and integrated materials with thematic titles, namely disasters, seasons, water, land, and earth. In this context, two main themes were identified, including (1) Natural Disasters, namely Hydrology, Geophysics, and Climatology prioritizing floods, landslides/volcanoes, and drought, respectively, and (2) Management Cycle focusing on several stages, such as mitigation, preparedness, and response. Conclusion: The Natural Disasters were experimentally identified, accompanied by integrating the management cycle into school textbooks for students with ID at SPS 1 Padang. This result explained that ID children learned lessons while preparing to encounter Natural Disasters, with preparedness institutionally considered through teachers active participation.